Development of a Landslide Observation System Using ZigBee Wireless Communication Technology - Kawamura, Youhei; Jang, Hyong Doo; Ohta, K.; Inagaki, Y. (American Society of Civil Engineers, 2016)
Extensive area of Japan is subjected to threats of potential landslides as roughly 70 percent of Japan consists of a steep mountainous terrain and moreover numerous artificial hill slopes are developed in residential areas. While various types of structural counter measures have been developed and successfully implemented in Japan, significant numbers of areas remain unprotected. Hence, non-structural measures, such as hazard maps and early warning systems, are required to minimize risks. One of the key technologies of the early warning system is the automatic detection system for landslides. In this research, we are developing an automatic detection system for landslides using ZigBee wireless communication technology. A general ZigBee-compliant platform made by Hitachi Co. Ltd. was customized and used in the constructing the wireless landslide detection system. The developed system monitors various environmental data, such as 3-axes acceleration, temperature, humidity, and illumination intensity. It was verified that all measured parameters except humidity were measured properly at an actual slope site with the proposed system.